Histological Structure of Gills of Giant Mudskipper (Periophthalmodon schlosseri) - Danang Bagus Yudistira; Anni Nurliani; Heri Budi Santoso (Jurnal Sain Veteriner, 2012)
Giant mudskipper (Periophthalmodon schlosseri) is one of gobiidae members that does air-breathing and lives on intertidal zone with mangrove habitat. The ability of giant mudskipper to adapt with water to land environment is due to its gill histological structure. The objective of the present study was to observe the structure of giant mudskipper’s gill and to identify sort of cells and its distributions descriptively. The gills of three adult giant mudskippers were taken and processed to histological slides with 4 µm thickness each. Samples were stained with hematoxyline-eosin (HE) method. The results indicated that Mudskipper  gills  consist  of epithelial cells, such as squamous and cuboid on the lamellae surfaces contiguous with mucous and chloride cells that are spread at interlamellae zone and peripheral surfaces of  fused  secondary  lamellae  of  mudskipper  gills.  Pillar  cells  sre found  inside  of  secondary lamellae and form lacunae that split secondary lamellae with block to block spaces that fill  with  erythrocytes.  Hyaline  cartilages  are   found  to form  canals  for  transport  veins inside  primary  lamellae  and  soft  muscle  connecting  hyaline to basal  membrane  of  primary lamellae surfaces. The difference of histological structures between giant mudskipper gills to other  aquatic osteichthyes is that  the  secondary lamellae  is fused  in  normal  (non-pathological)  condition. The fusion makes epithelial cells  of the econdary lamellae are thicker. The fusion  also makes oxygen diffusion path from water to capilary vein is a bit longer about 10µm. The  thickness of epithelial cells  of  secondary lamellae makes  the  mudskippers  gills not an efficient organ for gas exchanges in water, but it is important in osmoregulation. Keywords: Periophthalmodon schlosseri, air-breathing, histological structure, lamellae fusion, osmoregulation.